Modern Techniques and Solvents for the Extraction of Microbial Oils - Meullemiestre, Alice; Breil, Cassandra; Abert-Vian, Maryline; Chemat, Farid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
A valuable reference presenting many processes that facilitate lipid extraction from micro-organisms. Amongst the techniques included are Folch, Bligh and Dyer methods, and the Soxhlet technique as well as intensified green processes (ultrasound, microwave, supercritical fluid extraction, agro-solvent, accelerated solvent extraction, enzyme-assisted extraction, instant controlled pressure drop, pulse electric field). In addition to a section featuring the analysis of fatty acids by Gas Chromatography and lipids by High-Performance Thin-Layer Chromatography (HPTLC), this brief contains a valuable bibliography on microorganisms (classes, structures) and their applications as a source of value added oils and compounds for food and non-food applications such as biojet fuel.
Microorganisms: Source of High Value Added Compounds -- Analytical Methodology for Lipid Extraction and Quantification from Oleaginous Microorganisms -- Extraction Processes of Microbial Lipids -- Conclusion.
Keywords: Chemistry; Renewable energy resources; Analytical chemistry; Electrochemistry; Chemical engineering; Renewable energy sources; Alternate energy sources; Green energy industries; Chemistry; Industrial Chemistry/Chemical Engineering; Analytical Chemistry; Electrochemistry; Renewable and Green Energy; Electronic books